1999
DOI: 10.1111/j.1365-2621.1999.tb15928.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Molecular Properties of Egg‐white Lipid Films

Abstract: Polyethylene glycol-plasticized films were cast from alkaline (pH 11.25), heated (45 °C for 20 min), aqueous egg white (EW) solutions, with or without (10% or 20% w/w of EW) milkfat (two fractions), oleic acid, or egg yolk lysophospholipid (LPL). The lipids did not reduce (P > 0.05) film water vapor permeability. Oleic acid increased (P < 0.05) tensile strength and elongation, and surface sulfhydryl group (SH) concentrations in EW solutions. Oleic acid probably increased negative charges on EW proteins, unfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 34 publications
(50 reference statements)
2
26
1
1
Order By: Relevance
“…The differences between both proteins must be related to the higher surface hydrophobicity and free sulfhydryl content found for EW protein . In addition, heating has been reported to favor exposure of sulfhydryl groups located at EW protein surfaces …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between both proteins must be related to the higher surface hydrophobicity and free sulfhydryl content found for EW protein . In addition, heating has been reported to favor exposure of sulfhydryl groups located at EW protein surfaces …”
Section: Resultsmentioning
confidence: 99%
“…Tensile parameters ( σ m , ε f , E ) found in the present study for EW and SPI are in good agreement with those found elsewhere. 41, …”
Section: Resultsmentioning
confidence: 99%
“…Ovalbumin is the major protein fraction of albumin and the only one to contain free sulfhydryl (-SH) groups, which predominately affect gelation via reordering of its sulfur-sulfur bond at Cys 73 and Cys 120 (the 73rd and 120th amino acids in the primary structure of the protein, respectively) and its sulfur-hydrogen bonds at Cys 11 , Cys 30 , Cys 367 and Cys 382 (Margoshes 1990;Sun and Hayakawa 2002). In addition, the reduction in the pH of the egg dip prefry treatment probably acted to increase the number of free sulfhydryls available in the egg albumin, which other agents added to egg albumin have been shown to do (Handa et al 1999). Frying increased the number of free sulfhydryls present, which could have enhanced the ability of the egg albumin to form a film (Margoshes 1990; Sun and Hay- Asterisk (*) denotes significantly less moisture or lipid than the control at P < 0.05, double asterisk (**) denotes significantly more moisture or lipid than the control at P < 0.05.…”
Section: Justification For the Efficacy Of Dried Egg White As A Lipidmentioning
confidence: 99%
“…Our previous report indicated that cross‐linking of casein and zein hydrolysate did not affect the WVP of the film (Oh and others 2004). Moisture barrier properties of hydrophilic films can be improved by incorporating hydrophobic materials such as neutral lipids, waxes, and long chain saturated fatty acids (Weller and others 1998; Handa and others 1999; Tanaka and others 2001; Chick and Hernandez 2002; Bosquez‐Molina and others 2003). The hydrophobic materials can be introduced into films by either laminating the hydrophobic materials over the film or incorporating the lipid emulsion to films (Tanaka and others 2001).…”
Section: Introductionmentioning
confidence: 99%